Witchcraft : A Very Short Introduction - Gaskill, Malcolm (Oxford, New York Oxford University Press, 2010)
Throughout history, to the present day, witchcraft raises questions about the distinction between reality and fantasy, faith and proof. This Very Short Introduction explores witchcraft, both as a contemporary phenomenon and a historical subject. It looks at witch-beliefs and accusations around the world, from pre-history to the present.
Include Illustration, Reference and Index
Keywords: Witchcraft